1988
DOI: 10.1523/jneurosci.08-08-02986.1988
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of lesioned septal cholinergic neurons by nerve growth factor: specificity and requirement for chronic treatment

Abstract: We earlier reported that chronic intraventricular injections of NGF into adult rats with partial transection of the fimbria prevent the lesion-induced disappearance of cholinergic neurons in the medial septal nucleus and the diagonal band of Broca (Hefti, 1986). The present study assessed the specificity and treatment requirements of this effect of NGF. Immunohistochemical visualization of NGF receptors (NGF-R) revealed that these molecules are selectively located in forebrain cholinergic neurons of unlesioned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(81 citation statements)
references
References 55 publications
(91 reference statements)
4
76
1
Order By: Relevance
“…This is in agreement with the subsequently lower NGF levels, and that some NGF effects are not maintained after abolishing treatment. 31,32 The diseased AD brain environment also shows increased inflammatory responses and oxidative stress, 33 --35 which might affect cells negatively in implanted devices. However, the inflammatory environment in the AD brain is less severe than in the QA-lesioned rat and therefore cell viability is unlikely to be affected.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with the subsequently lower NGF levels, and that some NGF effects are not maintained after abolishing treatment. 31,32 The diseased AD brain environment also shows increased inflammatory responses and oxidative stress, 33 --35 which might affect cells negatively in implanted devices. However, the inflammatory environment in the AD brain is less severe than in the QA-lesioned rat and therefore cell viability is unlikely to be affected.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic intracerebroventricular infusion of NGF up-regulates ChAT gene expression and activity in the forebrain, thereby increasing ACh release (28-30). The trophic role played by NGF is evident because it prevents the death of cholinergic neurons in vivo after axotomy (31,32) and reverses the cognitive deficits associated with lesion-induced damage to cholinergic pathways (33). Further, targeted disruption of the high-affinity NGF receptor TrkA results in a developmental loss of 40% of ChAT-IR neurons in the medial septum associated with a doubling of the number of TUNELpositive neurons in the basal forebrain at P7 (34).…”
Section: Discussionmentioning
confidence: 99%
“…The problem of this neurotrophic factor, as with many other neurotrophic factors, is that it is a labile molecule with a short half-life, does not cross the BBB when administered systemically [72] and therefore needs to be administered directly to their target in the brain [73], and needs to be continuously administered since non-clinical studies have found that when NGF is withdrawn, its effects are not maintained [74,75].…”
Section: Monolithic Implantable Devices For Neurotrophic Factor Deliverymentioning
confidence: 99%